"Las comunicaciones y su influencia en el desarrollo tecnológico de la Universidad Técnica Estatal de Quevedo" - Macías Zambrano, Fausto Javier (2014)
The development of this research aims to implement the fiber optic backbone underground way and ensure the transmission of data to the benefit of technological development in the campus Ing. Manuel Alvarez Make State Technical University of Quevedo. An evaluation of the use of wires installed aerially was performed to determine the ideal operating them and providing services to the benefit of the university community. Security levels are implemented in the transmission of data by optical fiber ensuring data delivery with the lowest packet loss Similarly in order to improve the aesthetics and ease of maintenance the fiber optic backbone underground way ensuring noise immunity and overall redundancy in each of the nodes, thus meeting the objectives of computer networks was designed. Finally a ring network that supports voice, video and data so that all users can access these policies under established for the proper use and application of ICT for the benefit of institutional technological development has been set.